Photocatalytic CO2 reduction over metal-organic framework-based materials - Li, Dandan; Kassymova, Meruyert; Cai, Xuechao; Zang, Shuang-Quan; Jiang, Hai-Long (Coordination chemistry reviews, 2020)
In this review, we provide an overview of recent progress achieved in MOF-based photocatalysts for CO2 reduction on the basis of the reduced products. Diverse modification techniques for improving relevant photocatalytic performance and the corresponding structure-activity relationships are highlighted. Particular emphasis is placed on the role of CO2 capture capacity for the photocatalytic CO2 reduction performance over MOF-based materials. Furthermore, the opportunities, challenges and future prospects of the application of MOF-based materials for photocatalytic CO2 conversion have also been highlighted. [Display omitted] •An overview of research advances in photocatalytic CO2 reduction over MOF-based materials.•Key role of CO2 capture capacity in CO2 photoreduction performance over MOF-based materials.•The challenges and opportunities of MOF-based materials for photocatalytic CO2 reduction. Photocatalytic reduction of carbon dioxide (CO2) into high value-added chemicals using clean and renewable solar energy is a very promising pathway to address energy and environmental issues. Recently, metal-organic frameworks (MOFs) have been intensively exploited in photocatalytic CO2 reduction owing to their promising CO2 capture capability, photochemical and textural properties. In this review, we provide an overview of recent progress achieved in MOF-based photocatalysts for CO2 reduction on the basis of the reduced products, including photocatalytic conversion of CO2 into CO and the other organic chemicals (formic acid, methanol and methane). Diverse modification techniques for improving relevant photocatalytic performance and the corresponding structure-activity relationships are highlighted. Particular emphasis is placed on the role of CO2 capture capacity for the photocatalytic CO2 reduction performance over MOF-based materials. Furthermore, the opportunities, challenges and future prospects of the application of MOF-based materials for photocatalytic CO2 conversion are given, aiming at rational design of more creative MOF-based photocatalytic systems for CO2 utilization with a green and sustainable strategy.